2015
DOI: 10.1371/journal.pone.0134633
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Placental Plasmodium falciparum Malaria on the Profile of Some Oxidative Stress Biomarkers in Women Living in Yaoundé, Cameroon

Abstract: BackgroundImpact of the pathophysiology of Plasmodium falciparum placental malaria (PM) on the profile of some oxidative stress biomarkers and their relationship with poor pregnancy outcomes in women remain unknown.MethodsBetween 2013 and 2014, peripheral blood and placenta tissue from 120 Cameroonian women at delivery were assessed for maternal haemoglobin and, parasitaemia respectively. Parasite accumulation in the placenta was investigated histologically. The levels of oxidative stress biomarkers Malondiald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…In that work, the level of cell membrane lipid peroxidation, detected as malondialdehyde, was significantly increased in the placentas of malaria-infected and anemic women compared with noninfected and nonanemic counterparts (8). Moreover, oxidative stress was observed in a murine model of PM caused by P. berghei ANKA (911), which yields many features of human PM but is limited by parasite virulence and maternal mortality, restricting studies to late pregnancy.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In that work, the level of cell membrane lipid peroxidation, detected as malondialdehyde, was significantly increased in the placentas of malaria-infected and anemic women compared with noninfected and nonanemic counterparts (8). Moreover, oxidative stress was observed in a murine model of PM caused by P. berghei ANKA (911), which yields many features of human PM but is limited by parasite virulence and maternal mortality, restricting studies to late pregnancy.…”
Section: Introductionmentioning
confidence: 85%
“…In addition to these pathogenic findings in PM, a recent study showed that poor pregnancy outcomes may also be attributed to malaria-induced oxidative stress in the placenta (8). In that work, the level of cell membrane lipid peroxidation, detected as malondialdehyde, was significantly increased in the placentas of malaria-infected and anemic women compared with noninfected and nonanemic counterparts (8).…”
Section: Introductionmentioning
confidence: 99%
“…This oxidative stress has been reported in several placental disorders, pregnancy pathologies, and also in PAM [54, 55]. Malondialdehyde (MDA) is correlated positively with parasitaemia and NO is correlated negatively with birth weight [55]. sFlt-1 is also increased during PAM and associated with fetal loss, intra-uterine growth restriction, and placental inflammation.…”
Section: Introductionmentioning
confidence: 92%
“…Other factors, such as nitric oxide synthase, s-endoglin, or TGF-ß soluble receptor are associated to preeclampsia, but also to severe malaria in children and in infected primigravidae [44]. This oxidative stress has been reported in several placental disorders, pregnancy pathologies, and also in PAM [54, 55]. Malondialdehyde (MDA) is correlated positively with parasitaemia and NO is correlated negatively with birth weight [55].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a successful pregnancy is characterized by the predominance of anti-inflammatory cytokines at the feto-maternal interface that downregulates inflammatory response, which could be detrimental to the fetus [9]. Also, the accumulation of Plasmodium falciparum -infected erythrocytes and leucocytes in the placenta is associated with alteration in cytokine expression and some oxidative stress biomarkers profiles [10, 11]. The infiltrated leukocytes are the principal sources of inflammatory cytokines production [8, 12].…”
Section: Introductionmentioning
confidence: 99%